In silico discovery of novel cytotoxic T-lymphocyte epitopes in the HIV-1 Pol region in response to antiretroviral resistance mutations - Joubert, Fourie (University of Pretoria, 2015)
Thesis (PhD)--University of Pretoria, 2014.